PERLINDUNGAN HUKUM BAGI PEMBELI RUMAH UMUM DARI PERBUATAN WANPRESTASI OLEH DEVELOPER/PENGEMBANG SESUAI DENGAN UNDANG - UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Rani Shafira; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2019)
Housing or complex is a collection of houses as part of settlements, both urban and rural, equipped with infrastructure, facilities and public utilities as a result of efforts to fulfill livable houses. Nowadays housing development often happens and developers have begun to promote the building before the building was completed. Then after consumers do PPJB with the developer. But the problem that often arises is that developers have bad intentions with various things to the detriment of consumers. In this case the developer had a bad intention by guaranteeing violet garden consumer ownership certificates to Maybank to obtain a loan of funds which resulted in a loss for consumers. The problem that the author raises how is the responsibility of the developer who defaults on general home buyers according to UUPK? What is the legal protection for general home buyers from defaults carried out by developers according to UUPK? What are the obstacles and efforts of the government in implementing the UUPK against the default problems that the developer has made? The author examines this case with normative research methods. The results of the analysis obtained by the author state that the developer has defaulted on the consumer, the developer cannot be held responsible for his mistakes, the developer has violated his obligations as a business actor and the developer does not fulfill the consumer rights set out in the UUPK. Based on this case, the UUPK should be revised and consumers must be more careful in making home purchases.